2022
DOI: 10.14569/ijacsa.2022.0131103
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Micro Vascular and Macro Vascular Complications in Type-2 Diabetic Patients using Machine Learning Techniques

Abstract: A collection of metabolic conditions known as diabetes mellitus are defined by hyperglycemia brought on by deficiencies in insulin secretion, action, or both. In terms of mortality rate, type-2 diabetes is 20 times higher when compared with type-1. Based on the earlier research, there is still scope to identify different risk levels of type-2 diabetes complications. To achieve this, we have proposed a T2DC machine learning-based prediction system using a decision tree as a base estimator with random forest to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Besides, recent advances in medical diagnosis have witnessed a surge in the adoption of deep learning methods. Studies such as (Ahmad, Ai, et al, 2019; Ahmad, Ding, et al, 2019; Alzghoul et al, 2023; Bataineh, 2019; Doppala et al, 2023; Furqan Qadri et al, 2019; Habib & Qureshi, 2023; Hirra et al, 2021; Qadri et al, 2019; Qadri et al, 2021; Qadri et al, 2022; Qadri et al, 2023; Vamsi et al, 2022) have demonstrated deep learning ability in dealing with large datasets and complex patterns. While deep learning methods provide robust performance (Ahmadian et al, 2021; Arora et al, 2022; Jalali, Ahmadian, Ahmadian, et al, 2022; Jalali, Arora, Panigrahi, et al, 2022; Jalali, Osorio, Ahmadian, et al, 2022; Mehnatkesh et al, 2023; Saffari et al, 2023), their computational density and the need for extensive data and training can be limited in certain scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, recent advances in medical diagnosis have witnessed a surge in the adoption of deep learning methods. Studies such as (Ahmad, Ai, et al, 2019; Ahmad, Ding, et al, 2019; Alzghoul et al, 2023; Bataineh, 2019; Doppala et al, 2023; Furqan Qadri et al, 2019; Habib & Qureshi, 2023; Hirra et al, 2021; Qadri et al, 2019; Qadri et al, 2021; Qadri et al, 2022; Qadri et al, 2023; Vamsi et al, 2022) have demonstrated deep learning ability in dealing with large datasets and complex patterns. While deep learning methods provide robust performance (Ahmadian et al, 2021; Arora et al, 2022; Jalali, Ahmadian, Ahmadian, et al, 2022; Jalali, Arora, Panigrahi, et al, 2022; Jalali, Osorio, Ahmadian, et al, 2022; Mehnatkesh et al, 2023; Saffari et al, 2023), their computational density and the need for extensive data and training can be limited in certain scenarios.…”
Section: Introductionmentioning
confidence: 99%